Análisis de las características y preferencias académicas de los estudiantes del plan de estudio 232 de la Carrera de Administración de Empresas modalidad nocturna impartida en el Campus Tecnológico Local San José al primer semestre 2019 - Arias-Grijalba, David Josué (Instituto Tecnológico de Costa Rica., 2019)
The School of Business Administration of the Technological of Costa Rica (TEC) has offered for more than 40 years the career of Business Administration Nocturnal Modality Plan 232 for the population of the province of San José, said university belongs to the National Council of Rectors, which is regulated and budgeted by the Costa Rican State and the race is accredited by the SINAES. Currently, the career is coordinated by the Career Unit of Night Business Administration and lessons are taught at the San José Technology Campus. During all these years of trajectory, there are no monitoring studies or strategic indicators that explain the dynamics of the students, from the entry to the conclusion of the studies, including those who retire or drop out of the race; Only the figures reproduced by the Department of Admission and Registration in relation to enrollment, students who are rejected, approved and inactive, quantitative data that help to explain the reasons or circumstances faced by the student population are available. The study was developed to find the factors that affect the students of the race to the first semester 2019; The students were classified into three groups: active, inactive and graduated students; additionally, the 232 Plan was compared with all the academic offers in Career Administration accredited by the SINAES in Costa Rica. The research is Mixed, with a cross-sectional documentary research design with descriptive exploratory analyzes, in which the main variables of study were the personal, social and institutional determinants. It is concluded that the Career Unit of Night Business Administration does not know the percentages of graduates, students who are inactive and the advance in the curricula of the students who enroll. Likewise, it is concluded that there is a low percentage of students who complete their studies in time, there is a high percentage of inactive students and active students who do not carry their curriculum in order or enroll in complete blocks. The highest percentage of graduates were lagging students. In relation to the Plan 232 and its counterparts, it is determined that it is the second cheapest option, with the longest period of completion, it is the only nighttime race and its plan is made up of an important volume of courses.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2019.
Keywords: Instituto Tecnológico de Costa Rica. Campus Tecnológico Local San José; Educación superior; Administración de Empresas